2014
DOI: 10.1074/jbc.m114.549188
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule-facilitated Degradation of ANO1 Protein

Abstract: Background: The calcium-activated chloride channel ANO1 is highly expressed in cancer.Results: Inhibition of ANO1 activity alone is not sufficient to inhibit cancer cell proliferation, suggesting a novel function of ANO1 protein in cancer.Conclusion: The ANO1 inhibitor CaCCinh-A01 inhibits cancer cell proliferation by facilitating degradation of ANO1.Significance: Our results may provide a new targeting approach for antitumor therapy in ANO1-amplified cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…Previous studies have shown that pharmacological inhibition of ANO1 by small-molecule ANO1 inhibitors such as T16A inh -A01, CaCC inh -A01, tannic acid, MONNA and idebenone significantly decreased cell proliferation, migration or invasion abilities in human cancer cell lines expressing ANO1, even though the pathophysiological roles of ANO1 in cancer and the underlying molecular mechanisms of anticancer effect of downregulation of ANO1 are not clearly understood [12, 13, 23, 24]. Interestingly, as shown in Fig 5A and 5C, luteolin inhibited cell proliferation and migration of PC-3 human prostate cancer cells expressing high levels of ANO1 much more potently than that of ANO1-deficient PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that pharmacological inhibition of ANO1 by small-molecule ANO1 inhibitors such as T16A inh -A01, CaCC inh -A01, tannic acid, MONNA and idebenone significantly decreased cell proliferation, migration or invasion abilities in human cancer cell lines expressing ANO1, even though the pathophysiological roles of ANO1 in cancer and the underlying molecular mechanisms of anticancer effect of downregulation of ANO1 are not clearly understood [12, 13, 23, 24]. Interestingly, as shown in Fig 5A and 5C, luteolin inhibited cell proliferation and migration of PC-3 human prostate cancer cells expressing high levels of ANO1 much more potently than that of ANO1-deficient PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…FaDu cells were engineered to express control scrambled shRNA or TMEM16A-targeting shRNA in doxycycline-inducible manner as previously described by Britschgi, Bill et al [14, 15]. These cells were cultured in DMEM containing 10% tetracycline-free serum.…”
Section: Methodsmentioning
confidence: 99%
“…36 The non-selective CaCC inhibitor 1 was shown to accelerate the degradation of TMEM16A in cancer cells by the ubiquitin-proteasome pathway by a mechanism that may not involve channel inhibition. 37 Several recent studies address inhibitor selectivity. Studies of 1 , 2 , and 3 in isolated resistance arteries suggested poor TMEM16A selectivity for all three compounds.…”
Section: Introductionmentioning
confidence: 99%